Pertussis Toxin potentiates Th1 and Th2 responses to co-injected antigen: adjuvant action is associated with enhanced regulatory cytokine production and expression of the co-stimulatory molecules B7-1, B7-2 and CD28 - MILLS, KINGSTON (Oxford University Press, 1998)
Pertussis toxin (PT) is a major virulence factor of Bordetella pertussis which exerts a range of effects on the immune system, including the enhancement of IgE, IgA and IgG production, delayed-type hypersensitivity reactions, and the induction of experimental autoimmune diseases. However, the mechanism by which PT mediates adjuvanticity remains to be defined. In this investigation we have shown that PT can potentiate antigen-specific T cell proliferation and the secretion of IFN-gamma, IL-2, IL-4 and IL-5 when injected with foreign antigens. A chemically detoxified PT and a genetic mutant with substitutions/deletions in the S-1 and B oligomer components that abrogate enzymatic and binding activity displayed no adjuvant properties. In contrast, a non-toxic S-1 mutant devoid of enzymatic activity but still capable of receptor binding retained its adjuvanticity, augmenting the activation of both Th1 and Th2 subpopulations of T cells. In an attempt to address the mechanism of T cell activation, we found that PT stimulated the production of IFN-gamma and IL-2 by naive T cells and IL-1 by macrophages. Therefore potentiation of distinct T cell subpopulations may have resulted in part from the positive influence of IFN-gamma on the development of Th1 cells and the co-stimulatory role of IL-1 for Th2 cells. Furthermore, PT augmented expression of the co-stimulatory molecules B7-1 and B7-2 on macrophages and B cells, and CD28 on T cells, suggesting that the adjuvant effect may also be associated with facilitation of the second signal required for maximal T cell activation. This study demonstrates that the immunopotentiating properties of PT are largely independent of ADP-ribosyltransferase activity, but are dependent on receptor binding activity and appear to involve enhanced activation of T cells.
PUBLISHED
Keywords: Biochemistry